MOSQUITO-BORNE PARASITES IN PATIENTS NEWLY INFECTED WITH HIV IN RELATIONSHIP WITH CD4 COUNT AND TNF ALPHA - Olaniyan, Mathew Folaranmi (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Mosquito-borne parasites include the pathogenic protozoa and helminths that are transmitted by the insect vector which may co-infect with other organisms to elicit an immune response. Purpose: To determine the frequency of mosquito-borne parasites in patients newly infected with HIV in relationship with CD4 count and TNFα. Method: Thirty-one (31; aged 15-32 years; male-12; female-19) newly diagnosed HIV positive patients and fifty (50) age-matched HIV negative volunteers were recruited as a control subject for this study. All subjects were negative to anti-HCV/HBsAg ELISA, Plasmodium, Acid-Fast Bacilli (AFB) tests and the control subjects were also negative to HIVP24 Ag-Ab ELISA, Plasmodium spp. and Wuchereria bancrofti microscopy. Venous blood including Night blood samples and sputum samples were obtained from the participants for CD4 count by cyflowmetry, TNFα, HIVP24Ag-Ab, anti-HCV, HBsAg by ELISA and microscopic identification by Giemsa staining while Sputum sample was used for Ziehl Neelsen staining to demonstrate Acid Fast Bacilli (AFB). Result: A lower frequency of 25.8% (Rajan, 2008) Plasmodium spp. and 6.5% (James et al., 2015) W. bancrofti was obtained in newly infected HIV patients compared with 32% (Zeitlmann et al., 2001) Plasmodium spp. and 8% (WHO, 2019) W. bancrofti obtained in the non-HIV infected control subjects. Showed a significant decrease in CD4 count and increase in plasma TNFα in both HIV mono-infection and coinfection with Plasmodium spp. and W. bancrofti compared with the results obtained in the non-HIV infected control subjects (p<0.05) and the results obtained in the newly infected HIV patients without Plasmodium spp. and W. coinfection (p<0.05). Conclusion: There was a significant increase in plasma TNFα and a decrease in CD4 count in both HIV mono-infection and coinfection with Plasmodium spp. and W. bancrofti while a lower frequency of Plasmodium spp. and W. bancrofti was obtained in newly infected HIV patients compared with the results obtained in the non-HIV infected control subjects.